Outcomes Following Limb Crossing in Endovascular Aneurysm Repairs. (April 2015) - Dattani, Nikesh; Wild, John; Sidloff, David; Fishwick, Guy; Bown, Matthew; Choke, Edward; Sayers, Robert
Background: Crossing the limbs of the stent during endovascular aneurysm repair (EVAR) is often used to aid cannulation of the contralateral limb. This study assessed outcomes following the use of this technique. Methods: Retrospective review of crossed (n = 43) and uncrossed (n = 269) EVARs was performed at a tertiary vascular center over 5 years. Primary end points were graft limb occlusion (GLO), endoleak, and sac expansion rates. Indications for limb crossing were also assessed. Results: Two-year GLO ( P = .34) and type 1 endoleak ( P = .413) rates were similar between groups. Patients undergoing crossed EVAR experienced more type 2 endoleaks ( P = .002) at 24 months but no increase in sac expansion rates was observed ( P = .275). Thirty-day ( P = .57) and late ( P = .268) mortalities were similar between groups. The main indication for limb crossing was distal aortic angulation (48.8%). Conclusions: Crossed EVAR does not increase the risk of GLOs or clinically significant endoleaks. Further studies are needed to determine the effect on type 2 endoleak rates.